2020
DOI: 10.1149/1945-7111/ab7655
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Diagnostics for Li4Ti5O12-Based Lithium Ion Capacitors: Insights from a Physics-Based Model

Abstract: Lithium ion capacitors are an important energy storage technology, providing the optimum combination of power, energy and cycle life for high power applications. However, there has been minimal work on understanding how they degrade and how this should influence their design. In this work, a 1D electrochemical model of a lithium ion capacitor with activated carbon (AC) as the positive electrode and lithium titanium oxide (LTO) as the negative electrode is used to simulate the consequences of different degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This capacity fade in the AC/Li 4 Ti 5 O 12 -based LIC system may be due to the loss of the active material in the lithiated/de-lithiated state or due to the loss of Li inventory (LLI). 42 Particle cracking, development of resistive layers on the active sites during side reactions between the electrode and electrolyte, and also loss of electrical connectivity between particles may result in a dip in the active material content. Consumption of Li during decomposition and other parasitic reactions may result in LLI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This capacity fade in the AC/Li 4 Ti 5 O 12 -based LIC system may be due to the loss of the active material in the lithiated/de-lithiated state or due to the loss of Li inventory (LLI). 42 Particle cracking, development of resistive layers on the active sites during side reactions between the electrode and electrolyte, and also loss of electrical connectivity between particles may result in a dip in the active material content. Consumption of Li during decomposition and other parasitic reactions may result in LLI.…”
Section: Resultsmentioning
confidence: 99%
“…They conveyed that the prelithiation capacity range (C pl ) of 34 # C pl # 102 mA h g −1 with a mass ratio of 2 and an AC electrode potential of 3.0 V vs. Li + /Li represents the ideal prelithiation range of such a LIC. Recently, Madabattula et al 42,43 studied the need for prelithiation in AC/LTO using a theoretical model and analyzed the role of negative polarization in the AC cathode and the limit of prelithiation to improve the electrochemical performance. Furthermore, the model established a protocol for cycling the LIC without pre-lithiation to avoid the extra cost.…”
Section: Introductionmentioning
confidence: 99%
“…During cycling of a LIC in the given potential range, the cumulative precipitation effects could be one of the reasons for capacity fade at 10 C in higher mass ratio cells as observed in Dsoke et al 6 Further analysis on capacity fade in LICs is reported in a separate communication. 32 It is to be noted that the precipitation effects are dependent on the discharge current and utilization of the cell together.…”
Section: Resultsmentioning
confidence: 99%
“…It introduces noise into the input data and trains the network to reconstruct the original data without noise, thereby learning a more robust and resilient feature representation. To solve this problem, multiple DAEs can be used to reconstruct inputs containing noisy data [21]. The SDAE is engineered to acquire multi-level abstract features of the data [22].…”
Section: Stacked Denoised Autoencodermentioning
confidence: 99%